1997
DOI: 10.1126/science.275.5299.540
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for the Transcription Factor LSIRF/IRF4 for Mature B and T Lymphocyte Function

Abstract: Lymphocyte-specific interferon regulatory factor (LSIRF) (now called IRF4) is a transcription factor expressed only in lymphocytes. Mice deficient in IRF4 showed normal distribution of B and T lymphocyes at 4 to 5 weeks of age but developed progressive generalized lymphadenopathy. IRF4-deficient mice exhibited a profound reduction in serum immunoglobulin concentrations and did not mount detectable antibody responses. T lymphocyte function was also impaired in vivo; these mice could not generate cytotoxic or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
483
1
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 544 publications
(513 citation statements)
references
References 20 publications
23
483
1
6
Order By: Relevance
“…In Table 2 the expression of investigated B-cell transcription factors in normal B-cell development is displayed. [12][13][14][15][16][17][18][19][20][21][22][23] Early B-Cell Transcription Factors: Pax-5 and PU.1 Expression…”
Section: Resultsmentioning
confidence: 99%
“…In Table 2 the expression of investigated B-cell transcription factors in normal B-cell development is displayed. [12][13][14][15][16][17][18][19][20][21][22][23] Early B-Cell Transcription Factors: Pax-5 and PU.1 Expression…”
Section: Resultsmentioning
confidence: 99%
“…Defects in IRF4/MUM1 expression result in defects in lymphocytes (T and B cell) and terminal differentiation of B cells toward plasma cells. 30 In addition, IRF4/MUM1 expression correlates with poor prognosis in various B-cell lymphoproliferative disorders. IRF4/MUM1 in cooperation with PU-1 enhances the transcription of the monokine induced by interferon-gamma (MIG) gene.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have demonstrated that IRF-4 is a critical effector of mature lymphocyte function. 45 Imaizumi et al 46 have indicated that IRF-4 is involved in the pathogenesis of T-cell leukemia through its positive effect on the cell cycle, and that IRF-4 can be used as a molecular marker of clinical subtype in cell leukemia. An alternative explanation of altered expression of IFNg-regulated genes is provided by the fact that IFITM1 is notably associated with stem cells.…”
Section: Discussionmentioning
confidence: 99%